(untitled) (Revista Brasileira Multidisciplinar, 2024)
The thermal discomfort in buildings on hot days and the high levels of electricity expenditure in buildings with refrigeration systems have an economic and energetic impact on the maintenance of thermal comfort. This work presents a comparison of energy efficiency between a green roof and a fiber cement roof using a comparison carried out by temperature collection over a period of one month, highlighting the arboreal benefits and cost savings that the green roof can bring. Data collection was carried out over a period of one month at 7:00 am, 1:00 pm and 5:00 pm, measuring the temperature at these times in two reduced-scale prototypes, one with a green roof and the other with fiber cement tile. The green roof system proved to be efficient, reducing maximum temperatures and increasing minimum temperatures, keeping internal temperatures closer to current thermal performance standards.